International Response to Urge United States’ Carbon Reduction Commitment on Willow Project - Sebayang, Her Dianta Mehaga; Azaria, Davilla Prawidya (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
A large oil drilling project located in Alaska, United States, called Willow aims to explore significant oil reserves. Although the project is intended to increase fossil fuel production in the region, its impacts have raised concerns worldwide because of its potential to produce significant carbon emissions. These emissions could exacerbate climate change worldwide and threaten local Alaskan ecosystems, including flora and fauna that are vulnerable to noise and air pollution. These effects could also disrupt nearby communities that rely heavily on a clean and healthy environment. The Willow Project’s compliance with international environmental law—specifically the Paris Agreement—is evaluated through case study and normative juridical methods. One of the responsibilities of signatory countries to this agreement is to reduce carbon emissions that will limit global warming. The findings show that the Willow Project is in conflict with this commitment and shows that the United States is not on board with its efforts to combat climate change. In addition, the study examines how the Willow Project impacts human rights, particularly the right to a clean environment. Many issues relate to transparency and accountability because the public is not sufficiently involved in the decision-making process of the project. The results of this study confirm that stricter international regulations must be implemented and greater oversight is needed for high-risk energy projects. Therefore, the international community must push for decisive action to ensure environmental sustainability and human rights protection in the future.